Database in Land Resource Management. - SH.Y.Sattorov; A.M.Abdulloyev; A.B.Ochilov; T.A.Ismatov (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses the current importance of databases and land databases in land resource management.